Temperature and phosphorus: the main environmental factors affecting the seasonal variation of soil bacterial diversity in Nansi Lake Wetland - Chen, Lei; Shi, Yuying; Wang, Shen; Sun, Mengyao; Wang, Meng; Ren, Xiaoyue; Gao, Zenghao; Zhou, Yiping; Zhang, Jie; Zhuang, Weijing; Su, Xinyue; Fu, Yongchao; et al. (Frontiers in Microbiology, 2023)
The soil bacteria promote the circulation conversion of lake nutrients and play an important role in maintaining the balance of the lake ecosystem. Few studies have investigated the association of seasonal variation in bacteria and environmental factors in inland freshwater lake wetlands. Nansi Lake is a large shallow freshwater lake in northern China. It is an important hub of the eastern route of the South-to-North Water Diversion Project. In this study, bacterial 16S rRNA genes were used to analyze the variation of soil bacterial community diversity in Nansi Lake wetland and its influencing factors in different seasons. The results showed that the phylum, family and genus with the largest relative abundance in the soil of Nansi Lake wetland are Proteobacteria, Nitrosomonadaceae, and MND1, respectively. There were significant seasonal differences in soil bacterial diversity in Nansi Lake wetland, which was significantly higher in summer than in winter. Seasonal variation in environmental factors was significantly correlated with the variation in bacterial communities. Temperature and the content of available phosphorus may be the key factors influencing seasonal variation in bacterial diversity. The results of this study further enhance our understanding of the relationship between bacterial community diversity and environmental factors in the lake wetland ecosystem, which can provide scientific data for the conservation of Nansi Lake wetland.